Features of myocardial injury in severe organophosphate poisoning. (September 2014) - Cha, Y. S.; Kim, H.; Go, J.; Kim, T. H.; Kim, O. H.; Cha, K. C.; Lee, K. H.; Hwang, S. O.
Abstract: Background . In organophosphate (OP) poisoning cardiac complications may occur. However, the current body of knowledge largely consists of limited studies, and case reports are mainly on electrocardiogram (ECG) abnormalities. As definite myocardial injury is difficult to assess through ECG, we investigated the prevalence of myocardial injury through cardiac biochemical markers such as troponin I (TnI) in severe OP poisoning. Methods . We conducted a retrospective review of 99 consecutive OP insecticide poisoning cases that were diagnosed and treated at the emergency department of the Wonju Severance Christian Hospital between March 2008 and December 2013. Results . Based on Namba classification for OP poisoning, there were no patients with mild toxicity, 9 patients (9.1%) with moderate toxicity and 90 patients (90.9%) with severe toxicity. On ECG, normal sinus rhythm was most common, and ST depression and elevation were seen in 11 patients (11.1%). Elevation of TnI within 48 h was seen in 34 patients (34.3%). The median peak level and peak time of TnI were 0.305 (IQR, 0.078–2.335) ng/mL and 15 (IQR 6.9–34.4) hours, respectively. There were differences between patients with normal TnI and elevated TnI in terms of age (yrs), number of patients who were exposed to OP via the oral route, and initial Glasgow Coma Scale (GCS; 58 ± 17 vs. 66 ± 16, p = 0.015, 56 [87.5%] vs. 33 [97.1%], p = 0.048 and 12.0 [IQR, 8.0–15.0] vs. 9.0 [IQR, 5.8–12.0], p = 0.019). Conclusions . OP can cause direct myocardial injury during the acute early phase in severe OP poisoning. Monitoring of TnI may be needed in severe OP poisoning.